Modeling Public Trust in Acupuncture Therapy: Social Legitimacy, Healing Narratives, and Epistemic Trust with Perceived Therapeutic Credibility as a Mediating Variable - Chantika Mahadini (Newinera Publisher, 2026)
This study investigates the factors influencing Public Trust in acupuncture therapy, focusing on the roles of Social Legitimacy, Healing Narratives, and Epistemic Trust. Using a quantitative approach with a correlational research design, the study examines the relationships between these independent variables and Public Trust, with Perceived Therapeutic Credibility as a mediating variable. A Structural Equation Modeling (SEM) technique using Partial Least Squares (PLS) was employed to analyze the data. The research was conducted across five acupuncture clinics in Malang City, involving 150 patients with Low Back Pain (LBP). Data was collected using a structured questionnaire and purposive sampling. The study found that Healing Narratives had the most significant impact on Public Trust, supporting previous findings that personal stories and experiences are crucial in legitimizing complementary and alternative medicine. Both Social Legitimacy and Epistemic Trust directly influenced the Perceived Therapeutic Credibility and Public Trust, highlighting the importance of societal acceptance and the credibility of information surrounding acupuncture. Furthermore, Perceived Therapeutic Credibility was confirmed to mediate the relationships between Social Legitimacy, Healing Narratives, and Public Trust. However, the indirect effect of Epistemic Trust on Public Trust through Perceived Therapeutic Credibility was found to be non-significant. The study contributes to the understanding of how Public Trust in acupuncture is shaped, emphasizing the roles of social validation, narrative storytelling, and epistemic credibility. These findings offer practical insights for practitioners and policymakers aiming to enhance acupuncture’s acceptance in mainstream healthcare.